AN EXAMINATION OF CUSTOMER SATISFACTION: DIFFERENCES BETWEEN LOCAL AND FOREIGN CUSTOMERS - Eristia Lidia Paramita; Vicka Onthoni (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2021)
This study aims to provide a comparative analysis of local and foreign customers’ evaluation on their perception, perceived value, and customer satisfaction toward Gojek mobile application. Data was obtained by spreading the online questionnaire to 200 samples of local and foreign customers. By using quantitative analysis method and Independent Sample T-test, the study reveals that local and foreign customers share different evaluation of the mobile application, perception of service quality, price and trust, which lead to different satisfaction as well. Instead, perceived value on intention to use, perceived quality of service, perceived ease of use, perceived price and perceived usefulness has no difference between local and foreign customers. However, even they have shared nearly the same perceived value of Gojek mobile application, local customers sense the higher value in a whole examination compared to foreign customers. Keywords : Perception, Perceived Value, Customer Satisfaction, Mobile Application